Pengaruh Rasio Pencampuran Limbah Cair Tahu Dan Kotoran Sapi Terhadap Proses Anaerob - Putra, Hadi Purnama; Andrio, David; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Consentration of COD total from tofu wastewater were 3.305 mg/L, was not supplied COD optimum criteria for anaerobic wastewater treatment, so it was necessary added cow dug which has concentration of COD concentration 10.730 mg/L. The combination of both types of wastewater will effect for C/N ratio that affects the formation of volatile fatty acids and biogas. This research aimed study the effect of the composition of the mixture of tofu wastewater and cow dung to efficiency reduction in COD total of the anaerobic process. The study was conducted in semi-batch, using a reactor with a working volume of 20 and 5 liters, inoculum ratio: waste = 80%: 20%. Before being used as sources of inoculum from WWTP oil and cow's rumen acclimatized beforehand by 0%: 100%, 50%: 50%, and 100%: 0%. The research used varioation a mixing ratio in the range R1 = tofu wastewater (25%) : cow dug (75%), R2 = tofu wastewater (50%) : cow dug (50%), and R3 = tofu wastewater (75%) : cow dug (25%). The result showed the reduction of COD total highest in R1 ratio was 782,68 mg/L/day and the lowest in R3 ratio was 277,06 mg/L. Formation the highest of biogas produced by R1 ratio was 50,4 mL and the lowest by R3 ratio with no formation of biogas volume.Keywords : Anaerobic process, biogas, tofu wastewater, cow dung, inoculum